Zein nanoparticle stabilized Pickering emulsion enriched with cinnamon oil and its effects on pound cakes. (March 2020) - Feng, Xiao; Sun, Yujia; Yang, Yuyan; Zhou, Xin; Cen, Kaiyue; Yu, Chen; Xu, Tian; Tang, Xiaozhi
Abstract: Pickering emulsion enriched with cinnamon essential oil (EO) was applied to partially replace butter in pound cakes and to inhibit mold growth. Pickering emulsions stabilized by zein nanoparticles were dominated by elasticity (G' > Gʺ), indicating the formation of gel-like network microstructure. The aldehyde groups of cinnamaldehyde may interact with amino groups on zein nanoparticles at oil-water interface to enhance the viscoelastic properties of Pickering emulsions, which explained the increased storage modulus as the amount of EO increased. Pickering emulsion of 20 g zein nanoparticle solution (ZNS) +20 g sunflower oil significantly increased the hardness of pound cakes, while Pickering emulsion with 5 g EO addition maintained the texture and colour compared with control group. EO also exerted antimicrobial effect to pound cakes, as the yeasts and molds of 5 g and 10 g EO emulsion added cakes were 1.55 and 1.42 log CFU/g after 12-day room-temperature storage compared with 2.96 log CFU/g of control group. To conclude, Pickering emulsion of 20 g ZNS+15 g oil+5 g EO showed the best effect to replace 20% butter in pound cakes to lower the calorie intake and extend the shelf-life without altering the texture and colour. Highlights: Zein stabilized Pickering emulsion could replace 20% butter in pound cakes. Cinnamaldehyde may interact with amino group of zein at oil-water interface. The storage modulus of Pickering emulsions increased as the EO addition increased. Addition of 5 and 10 g EO extended the shelf-life for 4 and 12 days, respectively. Emulsion of 20 g ZNS+15 g oil+5 g EO didn't alter the texture and colour of cakes.